Pengaruh Penggunaan Artificial Intelligence (Ai) Terhadap Kemampuan Berpikir Kritis Mahasiswa Jurusan Pendidikan Ekonomi Angkatan 2022 Universitas Negeri Gorontalo - Nurlaela Karim; Melizubaida Mahmud; Imam Prawiranegara Gani; Frahmawati Bumulo; Fatmawaty Damiti (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2026)
This research aims to determine the effect of Artificial Intelligence (AI) usage on the critical thinking abilities of students in the Department of Economics Education, Class of 2022, Universitas Negeri Gorontalo. This research employs a quantitative, survey-based approach. The population consisted of all students in the Department of Economics Education, Class of 2022, Universitas Negeri Gorontalo, totaling 194 students. The sampling technique used was probability sampling with simple random sampling, yielding a sample of 66 students. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis techniques used simple linear regression. The descriptive analysis results indicate that the variable of Artificial Intelligence (AI) usage has its highest value for the frequency of Al use in completing coursework. Regarding the critical thinking ability variable, the highest indicator is in the elementary clarification aspect. The results show a positive and significant effect of Artificial Intelligence (AI) use on students' critical thinking abilities in the Department of Economics Education, Class of 2022, Universitas Negeri Gorontalo. The coefficient of determination indicates that the effect of Al use on students critical thinking abilities is 0.674 (67.4%), while the remaining 32.6% is influenced by factors outside the variables examined. The theoretical implications of this research strengthen the notion that Al-based technology in learning can support the development of students' critical thinking abilities through more effective processes of analysis, evaluation, and problem-solving In practice, the results iesearch contribute to students and lecturers by enabling them to utilizove learning support medium, thereby enhancing students crit ical abilitics, and learning independence